Relapses in patients with a systemic vasculitis. - Gordon, M; Luqmani, R; Adu, D; Greaves, I; Richards, N; Michael, J; Emery, P; Howie, A; Bacon, P (1993)
Treatment with cyclophosphamide and steroids has greatly improved survival in patients with systemic necrotizing vasculitis but does not always provide a complete cure. There are as yet few data on the incidence, pattern and outcome of relapses in these diseases. We studied relapses in 150 consecutive patients with an idiopathic necrotizing vasculitis: 12 with classical polyarteritis (CPAN); 95 with microscopic polyarteritis (MPA); 28 with Wegener's granulomatosis (WG); and 15 with limited Wegener's granulomatosis (LWG). The relapse rates and median time to relapse in months were: CPAN, 41.7%/33; MPA, 25.4%/24; WG, 44%/42; LWG, 52%/18. The clinical features of relapse were similar to or more aggressive than those of the original presentation in CPAN and LWG and included renal disease for the first time, but in MPA and WG, relapse involved less renal involvement in the majority of cases. Laboratory tests, although often positive at relapse, were unhelpful in its prediction. The considerable accumulative non-fatal relapse rate contrasts with the very good long-term survival rates, and confirms the importance of long-term follow-up in systemic vasculitis.